Long noncoding RNAs are dynamically regulated during β-cell mass expansion in mouse pregnancy and control β-cell proliferation in vitro. - Giorgia Sisino; Alex-Xianghua Zhou; Niklas Dahr; Alan Sabirsh; Mangala M Soundarapandian; Ranjan Perera; Erik Larsson-Lekholm; Maria Chiara Magnone; Magnus Althage; Björn Tyrberg (PLoS ONE)
Pregnancy is associated with increased β-cell proliferation driven by prolactin. Long noncoding RNAs (lncRNA) are the most abundant RNA species in the mammalian genome, yet, their functional importance is mainly elusive. Aims/hypothesis This study tests the hypothesis that lncRNAs regulate β-cell proliferation in response to prolactin in the context of β-cell mass compensation in pregnancy. Methods The expression profile of lncRNAs in mouse islets at day 14.5 of pregnancy was explored by a bioinformatics approach, further confirmed by quantitative PCR at different days of pregnancy, and islet specificity was evaluated by comparing expression in islets versus other tissues. In order to establish the role of the candidate lncRNAs we studied cell proliferation in mouse islets and the MIN6 β-cell line by EdU incorporation and cell count. Results We found that a group of lncRNAs is differentially regulated in mouse islets at 14.5 days of pregnancy. At different stages of pregnancy, these lncRNAs are dynamically expressed, and expression is prolactin dependent in mouse islets and MIN6 cells. One of those lncRNAs, Gm16308 (Lnc03), is dynamically regulated during pregnancy, prolactin-dependent and islet-enriched. Silencing Lnc03 in primary β-cells and MIN6 cells inhibits, whereas over-expression stimulates, proliferation even in the absence of prolactin, demonstrating that Lnc03 regulates β-cell growth. Conclusions/interpretation During pregnancy mouse islet proliferation is correlated with dynamic changes of lncRNA expression. In particular, Lnc03 regulates mouse β-cell proliferation and may be a crucial component of β-cell proliferation in β-cell mass adaptation in both health and disease.